CD47-SIRPα axis in cancer therapy: Precise delivery of CD47-targeted therapeutics and design of anti-phagocytic drug delivery systems - Junqiao Zhu; Chengyuan Cai; Jiaxin Li; Jisheng Xiao; Xiaopin Duan (Elsevier, 2022)
As a "marker of self", CD47 is expressed on the surface of all cells in humans, mice, and other mammals to inhibit phagocytic destruction of normal cells through interacting with signal regulatory protein α (SIRPα) on the macrophages and dendritic cells and sending a "don't eat me" signal. Unfortunately, multiple types of cancer cells take advantage of this "don't eat me" signal by overexpressing CD47 on their surface to evade recognition by the macrophages and avoid immune surveillance. Thus, the blockage of the CD47-SIRPα axis may be a promising therapeutic target for cancer therapy. However, CD47-targeted therapies can most likely cause serious side effects such as anemia due to the widespread expression of CD47 in normal tissues, thereby, the precise delivery of CD47-targeted therapeutics is a key part in increasing clinical efficacies and reducing side effects. In addition, the "don't eat me" signal can also be exploited to design anti-phagocytic drug delivery systems to enhance circulation time in blood and accumulation in tumor sites. In this review, we focus on the two parts of CD47-SIRPα axis in the tumor therapy, one is the accurate delivery of CD47-targeted therapeutics by well-designed delivery systems, the other is the rational design of CD47 based anti-phagocytic drug delivery systems.